A postmodern Post-feminism without Women - Binetti, María José (2021)
This article aims at showing the way in which the discursive constructivism and ethical relativism characteristic of postmodern feminism and post-feminism leads to a neo-liberal and conservative political agenda that threatens women’s sex-based rights. The article will especially focus on the thought of Paul-B Preciado as a post-feminist activist. It draws a comparison also with the work of Saba Mahmood. In such a context, we will point out the necessity of a neo-material and realist framework able to account for the ontological reality of women, and their irreducibility to social hetero-norms.